1984
DOI: 10.1063/1.1137671
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and angular efficiencies of a microchannel-plate position-sensitive detector

Abstract: This paper presents a characterization of a commercially available position-sensitive detector of energetic ions and neutrals. The detector consists of two microchannel plates followed by a resistive position-encoding anode. The work includes measurement of absolute efficiencies of H+, He+, and O+ ions in the energy range between 250 and 5000 eV, measurement of relative detection efficiencies as a function of particle impact angle, and a simple method for accurate measurement of the time at which a particle st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(58 citation statements)
references
References 9 publications
2
56
0
Order By: Relevance
“…Some ions pass through a grid-covered aperture, of length 1.91 cm in the direction parallel to the electron beam, in the bottom plate. These ions are then accelerated to an energy of 5.4 keV and subsequently impact a position-sensitive detector ͑PSD͒, comprising a pair of 25 mm diameter microchannel plates and a resistive-encoded anode, 13 which records their arrival times and positions. The ion arrival times are used to identify their mass-to-charge ratios and the ion arrival positions are used to determine the effectiveness of product ion collection.…”
Section: Apparatus and Experimental Methodsmentioning
confidence: 99%
“…Some ions pass through a grid-covered aperture, of length 1.91 cm in the direction parallel to the electron beam, in the bottom plate. These ions are then accelerated to an energy of 5.4 keV and subsequently impact a position-sensitive detector ͑PSD͒, comprising a pair of 25 mm diameter microchannel plates and a resistive-encoded anode, 13 which records their arrival times and positions. The ion arrival times are used to identify their mass-to-charge ratios and the ion arrival positions are used to determine the effectiveness of product ion collection.…”
Section: Apparatus and Experimental Methodsmentioning
confidence: 99%
“…The former creation process is a statistical process that depends, among others, on the kinetic energy of the ions. 28,29 The latter charge multiplication process depends on the configuration of the channelplates and the voltage applied across the plates. 14,30 In addition, it is important to note that ageing of the channelplates can cause deterioration of the charge multiplication process.…”
Section: Channelplate Efficiencymentioning
confidence: 99%
“…It attenuated the primary beam to less than 0.1% of the saturation limit of MCP. The particle energy dependence of the MCP quantum efficiency has been studied in many works [48][49][50][51][52]. They concluded that the quantum efficiency of MCP saturates and converges to a constant value when the particle energy exceeds a certain threshold.…”
Section: Methodsmentioning
confidence: 98%
“…They were covered with nearly transparent grids, which had negative voltage relative to the MCP front surfaces to maximize the detection efficiency [47,48]. The MCP for the projectile detection had a delay line anode to generate a position signal.…”
Section: Methodsmentioning
confidence: 99%